Restricted Mourning: Impact of the COVID-19 Pandemic on Funeral Services, Grief Rituals, and Prolonged Grief Symptoms - Mitima-Verloop, Huibertha B.; Mooren, Trudy T. M.; Kritikou, Maria E.; Boelen, Paul A. (Frontiers in Psychiatry, 2022)
Background: The COVID-19 pandemic has put various restrictions on grief rituals. Literature suggests that the restrictions on funerals and grief rituals may increase the chance of developing symptoms of prolonged grief (PG). In this study, we explored the possible impact of the pandemic on aspects of the funeral and grief rituals and examined their relationship with PG symptoms. Method: Bereaved individuals from different countries, who lost a loved one in the year prior to the pandemic (n=50) or during the pandemic (n=182), filled in an online questionnaire, including a rating of the impact of COVID-19 restrictions, five aspects of the funeral service, five aspects of grief rituals, and a measurement for PG symptoms. Results: Participants bereaved during the pandemic rated the impact of the restrictions on the experience of the funeral and grief rituals as negative. Nevertheless, no differences were found in attendance and evaluation of the funeral and grief rituals for people bereaved prior to vs. during the pandemic. Attendance and evaluation of the funeral services were related to levels of PG symptoms, whereas the performance and helpfulness of grief rituals were not related to these symptoms. Although not related to PG symptoms, half of the participants used helpful alternative rituals to cope with their loss. Discussion: Our study suggests that bereaved people respond resiliently to the COVID-19 pandemic, for example by creating alternative rituals to cope with their loss. Furthermore, it stresses the importance of looking beyond symptom levels when studying the importance of funeral and grief rituals.